Daur Optimal Hutan Tanaman Sengon Dalam Proyek Aforestasi: Review Hasil Penelitian Suharlan 1975 - Yonky Indrajaya (Jurnal Penelitian Kehutanan Wallacea, 2017)
Forests play an important role in climate change mitigation by absorbing carbon dioxide in the atmosphere. Additional revenue from carbon credits may change the optimal management of plantation forest. This research aims to analyze the optimal rotation of joint production of timber and carbon sequestration of sengon stand in Java. The method used in this research is the profit maximization of forest stand obtained from wood sales and carbon credits (i.e. Hartman rule as a modification of Faustmann rule). The results of this study showed that (1) the biological rotation of sengon forest in site quality (SQ) III and IV are 6 and 5 years respectively, (2) Financial rotations of sengon forest in SQ III and IV are 8 and 6 years respectively, and (3) Additonal income from carbon sales in afforestation project will not lengthen the optimal rotation of sengon plantation.